2022
DOI: 10.1021/acs.est.2c00681
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Non-DLVO Interactions on the Co-Transport of Functionalized Multiwalled Carbon Nanotubes and Soil Nanoparticles in Porous Media

Abstract: Derjaguin−Landau−Verwey−Overbeek (DLVO) theory is typically used to quantify surface interactions between engineered nanoparticles (ENPs), soil nanoparticles (SNPs), and/or porous media, which are used to assess environmental risk and fate of ENPs. This study investigates the co-transport behavior of functionalized multiwalled carbon nanotubes (MWCNTs) with positively (goethite nanoparticles, GNPs) and negatively (bentonite nanoparticles, BNPs) charged SNPs in quartz sand (QS). The presence of BNPs increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 86 publications
(123 reference statements)
1
5
0
Order By: Relevance
“…29 And it is confirmed that nanomaterials have a high surface area to volume ratio, which makes them attractive for adsorbing chemicals onto their surface via van der Waals forces, electrostatic interactions, or chemical bonding. [33][34][35] Therefore, these and other studies support the idea that the size of biochar particles affects the soil's hydrological properties, having complex interactions with the saturated hydraulic conductivity and the larger aggregate content. 36,37 When the biochar particle size is on the nanoscale, the specific surface area will be greater, and the number of active adsorption sites for chemicals and general reactivity will increase, 38 such as the capacity for inorganic ions.…”
Section: Introductionsupporting
confidence: 67%
“…29 And it is confirmed that nanomaterials have a high surface area to volume ratio, which makes them attractive for adsorbing chemicals onto their surface via van der Waals forces, electrostatic interactions, or chemical bonding. [33][34][35] Therefore, these and other studies support the idea that the size of biochar particles affects the soil's hydrological properties, having complex interactions with the saturated hydraulic conductivity and the larger aggregate content. 36,37 When the biochar particle size is on the nanoscale, the specific surface area will be greater, and the number of active adsorption sites for chemicals and general reactivity will increase, 38 such as the capacity for inorganic ions.…”
Section: Introductionsupporting
confidence: 67%
“…In order to calculate the adsorption energies of the various systems obtained after interactions, optimization of the gas molecule and the metal-doped fullerene nanocages are also necessary. 31 The thiourea (CH 4 N 2 S) gas molecule was optimized separately, and also, each of the surfaces, including the pure and doped fullerene surfaces, was geometrically optimized. The bond lengths of the optimized gas molecule and the pure fullerene surface were computed and are depicted in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Geometric equilibration and energy minimization have been initially administered as a medium of ensuring stability and sensitivity of the designed systems. In order to calculate the adsorption energies of the various systems obtained after interactions, optimization of the gas molecule and the metal-doped fullerene nanocages are also necessary . The thiourea (CH 4 N 2 S) gas molecule was optimized separately, and also, each of the surfaces, including the pure and doped fullerene surfaces, was geometrically optimized.…”
Section: Resultsmentioning
confidence: 99%
“…Although these attractive interactions were much shallower than primary minimum interactions, their magnitudes are comparable to primary minimum interactions when charge heterogeneities are considered. 74 The binding energy between the negatively charged B and positively charged BPCa was lower than that between BPCa and Ca 5 (PO 4 ) 3 OH, suggesting that the non-DLVO interactions were more significant than the electrostatic interaction. Moreover, in the presence of calcium and at high pH, heteroaggregation had a strong influence on FHC transport.…”
Section: Effect Of P Speciation On Electrostatic Potential Profiles A...mentioning
confidence: 93%